Analyzing Financial Inclusion and Credit Access in Underserved Communities with Interactive Analytics Dashboards - Md Saiful Islam; Mohammad Rasel Miah (Emerging Frontiers Library for The American Journal of Interdisciplinary Innovations and Research, 2025)
Financial inclusion has become a fundamental factor in socio-economic growth, empowering individuals and communities, especially those that do not have the facilities of traditional banking to obtain fundamental financial needs: credit, savings, and insurance. Due to the efforts at the global level to increase access, high disparities still exist among the underserved communities whereby a lack of financial literacy, institutional discrimination, and infrastructural barriers impact the righteous access to the credit market. This study examines how the various patterns of loan distribution, credit demand, and financial inclusion occur within underserved communities using data-driven methodologies and superior visualization tools. By studying the demand of loaning in different areas such as business, personal, educational, housing, and car loans; the study is able to conclude that the demand of credit is well spread amongst all these areas thus underlining the diversity of financial needs. Employing the interactive dashboard, filtering, and statistical methods, and the study equips stakeholders with practical information about the financial habits and preferences of borrowers and the need for inclusive lending patterns that will consider various credit needs. With data visualization and predictive analysis, this study illustrates how complicated financial data can be converted to results that are clear, comprehensible, and applicable to policy making and decision making by financial institutions as well as policymakers. Machine learning and AI-based techniques are also included in the methodology, which reinforces the reliability of loan risk evaluation, anticipates possible default patterns, and allows creating more effective models of credit distribution. The results support the significance of socially fair lending policies which reduce unbalanced socio-economical demands and financial feasibility and make the deprived community benefit credit access and develop empowerment, resiliency. Further, the study brings out the ethical and regulatory aspects of technological solutions implementation with respect to financial systems as they require fairness, transparency, and accountability. This study optimizes on the field of knowledge about financial inclusion by providing an effective framework of incorporating the aspects of technological innovation, data-driven analysis, and inclusive policy-making in the envisaged goal of a more transparent, sustainable, and equitable financial ecosystem. The findings of this study can be useful not only in research but also in everyday life at the financial and policymaking levels and thus can be used as a resource to interested stakeholders to reduce the disparity between financial availability and socio-economic advances.